Urinary tract obstruction in the second trimester: a report of an incarcerated gravid uterus. Issue 9 (29th September 2022) - Morais, Mariana; Moura, Mário; Correia, Ana; Fan, Yida
Abstract : Incarceration of the gravid uterus (IGU) is a rare obstetric disorder that may lead to pregnancy-related complications. Acute urinary retention (AUR) is one of the associated symptoms in IGU and it is mostly observed in the first semester and early second trimester. A case of a woman, in her 30s, is described, who presented AUR and lower abdominal pain in the early second trimester. The diagnosis was confirmed upon pelvic examination, and abdominal and transvaginal ultrasound. Management included long-term bladder catheterisation, manual reduction manoeuvres and passive positioning manoeuvres at home. At 24 weeks of gestation, the uterus returned in its correct polarity, the Foley catheter was removed and the patient was able to void spontaneously. A healthy infant was delivered vaginally at term. No specific guidelines have been published for IGU treatment. However, prompt diagnosis and tight follow-up of these patients are essential to define strategies, reduce complications and prevent recurrences.